Web-Based Classification Information System For Web-Based at PT. Sintech Berkah Abadi - Sri Rahayu; Haris Haris; Yeni Candrah (ADI Publisher, 2021)
ABSTRACT PT. Sintech Berkah Abadi is one of the providers of software solutions in the global market, providing business-based and high-tech solutions for customers throughout Indonesia. At present in terms of archiving data that is accessed is still using a manual system and not yet computerized, the process of searching for archives is quite time consuming and making reports still uses Microsoft Excel. This study aims to design a web-based archival classification information system to make it easier to manage file management properly. In this study using data collection methods namely observation, interviews and literature study. In the system analysis method used is the SWOT analysis, the design method used is Extreme Programming (XP). The results of the system design by using a web-based system can facilitate users in inputting data, storing data, searching for data, and making more accurate archive reports, so that archiving can run effectively and efficiently. Keywords: Filing Information System, Classification, Search